Multiscale electrostatic embedding simulations for modeling structure and dynamics of molecules in solution: A tutorial review. Issue 21 (16th July 2020) - Dohn, Asmus O.
Abstract: The main concepts and important technical details of electrostatic embedding quantum mechanics/molecular mechanics (QM/MM) simulations are explained and illustrated with the intent of assisting newcomers in performing and gauging the accuracy of such simulations, focused on smaller molecules in solution. Beginners are advised on how to increase the reliability and accuracy of the simulations through benchmarking. Central considerations on methodologies for QM/MM Molecular Dynamics (MD) simulations are presented, alongside technical fundamentals regarding the construction and manipulation of simulation systems using the python‐based Atomic Simulation Environment (ASE). A worked example of QM/MM Born–Oppenheimer MD is included, and a flowchart summarizing the most salient decisions and tasks within the methodology is presented. Abstract : Main concepts and central technical details of electrostatic embedding quantum mechanics / molecular mechanics (QM/MM) simulations are explained and illustrated to assist newcomers in performing and gauging the accuracy of such simulations. Central considerations on methodologies for QM/MM Born‐Oppenheimer Molecular Dynamics (BOMD) simulations are presented, alongside technical fundamentals regarding the construction and manipulation of simulation systems using the python‐based Atomic Simulation Environment. A working example of running a QM/MM BOMD simulation is included.